(untitled) (UNED Research Journal, 2019)
In neotropical forests, the feeding habits of the white-faced monkey are widely known. However, little information is available regarding their diet and behavior in high-elevation tropical forests. Here I document (by photos) the consumption of the fruit of Hedyosmum mexicanum by a troop of Cebus imitator, on the slopes of Barva Volcano, Costa Rica, 2 625m above sea level.